ULTRASTRUCTURAL ASPECTS AND PROGRAMMED CELL DEATH IN THE TAPETAL CELLS OF LATHYRUS UNDULATUS BOIS - (:unkn) unknown (AKADEMIAI KIADO RT, 2012)
Programmed cell death (PCD) in the tapetum of Lathyrus undulatus L. was analyzed based on light, fluorescence and electron microscopy to characterize its spatial and temporal occurrence. Development and processes of PCD in secretory tapetal cells of Lathyrus undulatus L. were correlated with the sporogenous cells and pollen grains. At early stages of development the tapetal cells appeared similar to pollen mother cells, structurally. Concurrent with meiosis, tapetum expanded both tangentially and radially as vacuoles increased in size. Tapetal cells most fully developed at young microspore stage. However, tapetum underwent substantial changes in cell organization including nucleus morphology monitored by DAPI. The TUNEL staining confirmed the occurrence of intra-nucleosomal DNA cleavage. In addition to nuclear degeneration which is the first hallmark of PCD other diagnostic features were observed at vacuolated microspore stage intensely; such as chromatin condensation at the periphery of the nucleus, nuclear membrane degeneration, chromatin release to the cytoplasm, vacuole collapse according to tonoplast rupture, shrinkage of the cytoplasm, the increase and enlargement of the endoplasmic reticulum cisternae and disruption of the plasma membrane. After vacuole collapse due to possible release of hydrolytic enzymes the cell components degraded. Tapetal cells completely degenerated at bicellular pollen stage.
Keywords: Lathyrus undulatus Boiss.; programmed cell death; tapetum; TUNEL; vacuole collapse; POLLEN DEVELOPMENT; TRACHEARY ELEMENTS; ANTHER DEHISCENCE; PLANTS; DIFFERENTIATION; DEGENERATION; APOPTOSIS; RICE; WALL; PCD